Guagua Convention Center and Educational Park - Balauitan, Amado Jr. S.; Sundiang, Cynthia (Quezon City College of Architecture, University of the Philippines Diliman, 2001)
The thesis is about a problem solving and an action-provoking plan of an educational park system. In such manner it would start from one chain to another till it completes a loop in all regions of the Philippines. The thesis is to create a template of a Convention Center and Educational Park. The goal of the thesis is to provide support to the primary and secondary schools of a municipal and could hold as a center of education of the region. In such manner, equality among all schools is achieved by having access to such park. Most of the schools are public schools and are not being able to own such facilities such as library, sports buildings and others. Through the educational park, all students may have the privilege to use the said facilities. In the creation of an Educational Park, it does not only support a municipality but the whole region.
As we all we know, the Philippines suffers in a crisis and great losses of the professionals in the country (brain drain). In such thesis, it would help educate the youth to become more optimistic, righteous, and good citizens of the country.
The thesis is to study a municipality, trying to determine the culture and how to help guide the youth to become better living persons as they grow up, by the Convention Center and Educational Park.
In the Convention Center and Educational Park, it is not only knowledge and intelligence is developed for the users, but also wisdom, love, camaraderie, and social awareness.
In the hope of building new generations of Filipinos with good morals and values, our country may have the chance to reform and to redevelop. With the help of the guidance of the elders, may the youth learn and develop the rich culture of our country.
Vita.
Thesis (Bachelor of Landscape Architecture)--University of the Philippines Diliman.
Keywords: Convention facilities -- Guagua (Pampanga); Parks -- Guagua (Pampanga)